Sistem Informasi Pemesanan Ojek/Transportasi Online Berbasis Web - Anisa Nurfitria (Universitas Labuhanbatu, 2021)
The development of technology and communication greatly helps the organization's performance and business processes. Its development must produce benefits for the organization in obtaining the required information quickly so that it helps the organization manager in making decisions. Changes in the form of business processes that are used with the development of technology and communication are expected to be able to encourage organizations to have better management, one of which is the online transportation ordering service business. Therefore in this research a program will be developed, so that it can support the marketing process and sales transactions through internet media. For software development methods, using structured methods, namely Data Flow Diagrams and Entity Relationship Diagrams. For programming languages using PHP, while for databases using MySQL / XAMPP. The method used in building this application is the waterfall method, proposing an approach to systematic and sequential software development that starts at the level and progress of the system throughout all analysis, design, code, testing and maintenance.